Spectroscopic, molecular docking and semi-empirical studies of the Albumin binding activities of 5-Hydroxymethylfurfural and its synthesized derivative, Di (5-Furfural) Ether (2022)
Previous studies have investigated the safety of the food/drug additive, 5-hydroxymethylfurfural including its albumin binding which might impact on its biodistribution and toxicity. In contrast, the safety assessment of its major degradant, di (5-furfural) ether (OMBF) is often neglected despite having been detected at concentrations in excess of HMF in parenteral solutions. The aim of this study was to compare the albumin binding characteristics of OMBF with 5-hydroxymethylfurfural. OMBF was synthesized by thermal dehydration of 5-hydroxymethylfurfural and characterized by using spectroscopic and mass spectral techniques. The binding characteristics of 5-hydroxymethylfurfural and OMBF with bovine serum albumin (BSA) were elucidated by using UV-visible spectroscopy, molecular docking, and semi-empirical calculations. Photometric titrations with OMBF revealed more pronounced perturbations in the UV-visible spectra of BSA and binding constants that were 51% greater than those of 5-hydroxymethylfurfural. Thermodynamic parameters revealed that the OMBF binding to albumin was spontaneous and hydrophobic interactions were the main forces responsible for complex stabilization. Docking studies showed that the superior binding affinity of OMBF was due to its higher C/H ratio which facilitated an extensive network of six hydrophobic interactions with Tyr149, Leu237, Ala290, Ile289, and Arg194 residues of BSA Site I compared with only two hydrophobic interactions in 5-hydroxymethylfurfural complex. Analysis of the multi-point hydrogen bonded complexes by using PM6-D3H+ method revealed the interaction energy of OMBF-BSA complex was 1.5 folds greater than 5-hydroxymethylfurfural-BSA. The study confirmed an increased avidity and stability in the complexation of albumin with OMBF compared with 5-hydroxymethylfurfural. Stricter limits control of OMBF in heatprocessed foods/drugs is necessary.